Constructing Female Leadership Through Andromache of Scythia’s Character: A Representation Study of Old Guard 2 - Herliyanti, Serly; Andina, Diah Maya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the construction of female leadership in The Old Guard 2 throughthe character of Andromache of Scythia. Although recent scholarship highlightsincreased visibility of women leaders in action cinema, many portrayals remainnarratively marginal or symbolically constrained. Addressing this gap, the studyemploys a qualitative descriptive–interpretative design grounded in textual analysisand Stuart Hall’s constructionist theory of representation, complemented bycontemporary female leadership frameworks. Data were analyzed through systematicscene-based examination of visual and verbal signs related to authority, ethics,relationality, and collective action. The findings demonstrate that Andromache’sleadership is constructed as legitimate, ethical, relational, and enduring, independentof physical dominance. Female authority is normalized through narrative recognition,emotional competence, and collective orientation. The study concludes that The OldGuard 2 offers a progressive representation of female leadership that challengesconventional gendered norms in action cinema.